Dynamic Identification as a Tool to Constrain Numerical Models for Structural Analysis of Historical Buildings - Lacanna, G.; Betti, M.; Ripepe, M.; Bartoli, G. (Frontiers in Built Environment, 2020)
In recent few decades, operational modal analysis (OMA), also known as output-only or ambient vibration test (AVT), has become a powerful tool for a wide range of applications in the field of civil engineering. The output-only modal test represents an effective alternative to forced vibration techniques when historical structures are investigated. This method takes advantages from natural sources of vibration (wind, traffic, etc.) instead of having to shake the structure artificially. This paper shows how the dynamic characteristics of a building (i.e. frequency, modal shapes and damping ratios) can be automatically identified by enhanced frequency domain decomposition (EFDD) technique. The assessment of the dynamic characteristics is performed analyzing the Baptistery of San Giovanni in Firenze (Italy) where a network of seismic sensors was temporarily installed. The modal parameters are used to calibrate a 3D finite element (FE) numerical model, by using a genetic algorithm (GA). This procedure allows to obtain accurate and robust model capable to reproduce the actual dynamic behavior of the structure by minimizing the uncertainties related to the mechanical parameters. This paper, providing an illustrative case study in the field of health monitoring of monumental structures, confirms that the OMA technique is able to derive effective information on the dynamic behavior of the analyzed building, which is useful to tune reliable and robust numerical models to be employed for structural analysis.